2017
DOI: 10.1371/journal.pone.0180294
|View full text |Cite
|
Sign up to set email alerts
|

Physician communication coaching effects on patient experience

Abstract: BackgroundExcellent communication is a necessary component of high-quality health care. We aimed to determine whether a training module could improve patients’ perceptions of physician communication behaviors, as measured by change over time in domains of patient experience scores related to physician communication.Study designWe designed a comprehensive physician-training module focused on improving specific “etiquette-based” physician communication skills through standardized simulations and physician coachi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 41 publications
0
22
0
Order By: Relevance
“… 24 It has been demonstrated that an open and sincere dialog between the people involved in the patient’s management improves the functional outcome of many pathologies, including those involving rehabilitation. 25 29 However, few studies have tried to propose communication strategies and appropriate training to guide doctors to effective, empathic, and patient-centered communication, 30 , 31 so the relationship between the doctor, patient, and his/her social network is still strongly dependent on their subjective tendencies and respective capacities for empathic relationships.…”
Section: Discussionmentioning
confidence: 99%
“… 24 It has been demonstrated that an open and sincere dialog between the people involved in the patient’s management improves the functional outcome of many pathologies, including those involving rehabilitation. 25 29 However, few studies have tried to propose communication strategies and appropriate training to guide doctors to effective, empathic, and patient-centered communication, 30 , 31 so the relationship between the doctor, patient, and his/her social network is still strongly dependent on their subjective tendencies and respective capacities for empathic relationships.…”
Section: Discussionmentioning
confidence: 99%
“…The current body of literature suggests that a multi-faceted approach that includes elements of communication skills training, real-time feedback, and coaching is ideal. 14 Efforts that are sustained over time 12 and that address all clinical providers who influence patient satisfaction (i.e. residents, advanced practice providers and consulting physicians) have also met with success.…”
Section: Discussionmentioning
confidence: 99%
“…The target intervention population for 18 studies were doctors, and predominantly primary care providers/general practitioners. 26,28,34,35,37,39,46,47,49,50,55,56,[58][59][60][65][66][67] To be included and eligible to participate in an intervention, primary care providers often needed to treat a specific subset of patients in their practice. For example, Presseau et al focused on general practitioners who provided care to patients with type 2 diabetes across 44 general practices through a national cohort study.…”
Section: Provider and Health Setting Characteristicsmentioning
confidence: 99%